Signal Activation of Hepatitis B Virus–Related Hepatocarcinogenesis by Up-regulation of SUV39h1. (9th June 2020) - Takeuchi, Yasue; Tsuge, Masataka; Tsushima, Ken; Suehiro, Yosuke; Fujino, Hatsue; Ono, Atsushi; Yamauchi, Masami; Makokha, Grace Naswa; Nakahara, Takashi; Murakami, Eisuke; Abe-Chayama, Hiromi; Kawaoka, Tomokazu; et al.
Abstract: Background: Hepatitis B virus (HBV) X (HBx) protein is associated with hepatocellular carcinogenesis via the induction of malignant transformation and mitochondrial dysfunction. However, the association between HBx and histone methyltransferase in carcinogenesis has not been fully clarified. In the current study, we analyzed the association between HBx and the histone methyltransferase suppressor of variegation 3–9 homolog 1 (SUV39h1) using HBV replication models. Methods: We constructed several HBx and SUV39h1 expression plasmids and analyzed the association between HBx and SUV39h1 with respect to HBV replication and hepatocarcinogenesis. Results: SUV39h1 up-regulation was observed in HBV-infected humanized mouse livers and clinical HBV-related hepatocellular carcinoma tissues, indicating that SUV39h1 expression might be regulated by HBV infection. Through in vitro analysis, we determined that the coactivator domain of HBx interacts with the PSET (PostSET) and SET (Su(var)3-9, Enhancer-of-zeste, Trithorax) domains of SUV39h1. The expression levels of 4 genes, activating transcription factor 6, α-fetoprotein, growth arrest and DNA damage–inducible 45a, and dual-specificity phosphatase 1, known to induce carcinogenesis via HBx expression, were up-regulated by HBx and further up-regulated in the presence of both HBx and SUV39h1. Furthermore, histone methyltransferase activity, the main function of SUV39h1, was enhanced in the presence of HBx. Conclusions: We demonstrated that SUV39h1 and HBx enhance each other's activity, leading to HBx-mediated hepatocarcinogenesis. We propose that regulation of this interaction could help suppress development of hepatocellular carcinoma. Abstract : The histone methyltransferase suppressor of variegation 3–9 homolog 1 (SUV39h1) was upregulated by long term hepatitis B virus (HBV) infection. Their upregulation could enhance HBV-related hepatocarcinogenesis by activating their functions through the interaction with HBV X (HBx) protein.